Pengembangan Bahan Ajar Berbasis Discovery Learning Berorientasi Komunikasi Ilmiah Pada Materi IPA Kelas 5 Sekolah Dasar - Maulida, Isna; Mulyawati, Ima (Jurnal Paedagogy, 2023)
This study aims to develop teaching materials based on discovery learning oriented to scientific communication on science material of changing the form of objects for grade 5 elementary school students. This research usedÂ the Research and DevelopmentÂ (R&D) method with the ADDIE model. The subjects of this study were 30 grade 5 students of SDN Samudrajaya 01. Data collection techniques were carried out by validation tests from linguists, material experts, students, and teachers through questionnaires, responses, and direct observation during learning. This research data analysis technique used quantitative and qualitative descriptive analysis. The results of this study showed that the language validation score got 100%, including the very decent category that puts in a very high-quality range. The material validation results showing a success rate of 89% of the category were very feasible. The teacher’s response received a score of 96% in the very decent category, while students received the very decent category with a score of 97%. In the results of scientific communication, students scored 86% in the very good category. So, discovery-based teaching material productsÂ areÂ oriented towards scientific communication; material changes in the form of objects are feasible and can be applied in the learning process.